Greening Europe: 2022 European Public Investment Outlook - FLORIANA MARGHERITA CERNIGLIA; Francesco Saraceno (Open Book Publishers, 2022)
The third installment of the 'European Public Investment Outlook' series is an important and timely publication that draws together recent analyses to recommend significant increases in public investment in green ventures. Compelling data from key economists affiliated with international organizations like the International Monetary Fund, European Investment Bank and the European Commission, as well as academic departments and policy institutes are a clarion call for green investment to boost the economy and put the planet on a sustainable path. Like its predecessors, the book presents the issues in a lucid and navigable manner. Part I explores the EU's current levels of green public investment, as well as the challenges ahead in achieving net zero carbon emissions after years of decreasing funding and the obstacles presented by the COVID-19 pandemic and the Russian invasion of Ukraine. The public investment trends of France, Germany, Italy and Spain are systematically evaluated, as well as the REPowerEU policy – accelerated in Spring 2022 – to move away from Russia's supply of fossil fuels. Part II focuses on the investment needed for green transition; the important economic and fiscal effects and benefits this would bring; and the reality of what is required before 2030 to achieve the EU's carbon-neutral targets by 2050. Greening Europe is essential reading for economists, environmentalists, and policymakers. It should also be of interest to anyone who wants to understand the cost implications of the 'carbon-neutral' policies that governments have promised, and the urgent need to change our approach towards energy usage.
Keywords: 330; European Public Investment Outlook; public investment; green ventures; international organizations; International Monetary Fund; European Investment Bank; European Commission; academic departments; policy institutes; economy; sustainable path